Social support from evaluative familiar persons – a buffer against stress? Preliminary evidence of neuroendocrine and psychological responses. Issue 5 (3rd September 2019) - Mascret, Nicolas; Vors, Olivier; Marqueste, Tanguy; Casanova, Rémy; Cury, François
ABSTRACT: Background and Objectives: Social support may have a stress-buffering effect when an individual is or could be negatively judged by others, but paradoxically may also exacerbate stress. The aim of our study was to examine these findings when social support was provided by a positive or negative evaluative audience composed of familiar and close others (teachers). Design and Methods: 84 men were confronted with the Trier Social Stress Test for Groups through a 3 (negative, positive, no-audience) x 2 (familiar, unfamiliar) experimental design with four measurement points of cortisol levels and state anxiety. We also tested whether closeness with the committee members predicted these variables for the participants in the familiar conditions. Results: Using both a frequentist and a Bayesian approach, familiarity and social support did not have stress-buffering effects (or merely anecdotal effects) on cortisol levels but buffered self-reported anxiety only for the participants faced with a supportive audience composed of familiar persons. Closeness with the experimenters was not a significant predictor of the stress responses. Conclusions: Because these results are preliminary evidence, further investigations into the relations between support provider and recipient during evaluative tasks would be worthwhile to better explain opposing findings found in this growing literature.